Silicon-based composite material, negative electrode and battery

By using the combination of silicon-carbon composite particles and sustained-release substances in the silicon-based negative electrode battery, the structural damage caused by volume expansion during charging and discharging of the silicon-based negative electrode battery is solved, and the cycle stability and life of the battery are significantly improved.

CN119725423APending Publication Date: 2025-03-28LANXI ZHIDE ADVANCED MATERIALS CO LTD

Patent Information

Application Number
CN202311283869.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The volume expansion of existing silicon-based negative electrode batteries during charging and discharging leads to structural damage, poor cycle stability and short cycle life, which limits their large-scale commercial applications.

Method used

Using a combination of silicon-carbon composite particles and sustained-release substances, the silicon-carbon composite particles are composed of a porous carbon carrier and a silicon nanomaterial loaded in its pores. The sustained-release substance is coated on the surface of the silicon-carbon composite particles or dispersed in its three-dimensional network structure to form a sustained-release layer or three-dimensional network structure.

Benefits of technology

Through the slow lithium ion release of the sustained release substance, the cycle life and capacity retention of the electrode are improved, the electrochemical performance is optimized, and the cycle stability of the battery is significantly extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725423A_ABST
    Figure CN119725423A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-based composite material, a negative electrode and a battery. The silicon-based composite material comprises silicon-carbon composite material particles and a slow-release substance, the silicon-carbon composite material particles comprise porous carbon and a silicon nanomaterial loaded in pores of the porous carbon, and the slow-release substance coats the outer surfaces of the silicon-carbon composite material particles to form a slow-release layer; or the slow-release substance has a three-dimensional network structure in a micron size, and the silicon-carbon composite material particles are dispersed in the three-dimensional network structure of the slow-release substance. The slow-release substance can slowly release lithium ions, so that the capacity retention ratio is maintained at a relatively high level, the cycle life of an electrode is greatly prolonged, and the silicon-based composite material can show excellent cycle performance when being applied to a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a silicon-based composite material, a negative electrode and a battery. Background Art

[0002] Silicon has an extremely high theoretical specific capacity and can form Li 15 Si4 alloy has a theoretical capacity of 3579mAh / g and is expected to replace traditional graphite negative electrode and become the next generation of high-energy-density lithium-ion battery negative electrode material.

[0003] However, silicon undergoes huge volume expansion / contraction during the lithium insertion / extraction process, which leads to electrode structure damage, battery capacity attenuation, and reduced cycle efficiency, thus hindering the practical application of silicon anodes. The volume expansion of silicon can be reduced or alleviated and the electrochemical performance can be improved by nano-scaling, composite and coating treatment of silicon materials, but the cycle life of silicon-based anodes is still not enough for large-scale commercial applications.

[0004] In the prior art, the patent with publication number CN102214817A discloses a carbon / silicon / carbon nanocomposite structure negative electrode material and its preparation method, the negative electrode material is composed of a carbon-based conductive matrix, nano-silicon uniformly distributed on the carbon-based conductive matrix and a nano-carbon coating layer on the surface of the nano-silicon, and the preparation method is to sequentially deposit nano-silicon and a coating nano-carbon layer on the carbon-based conductive matrix by a chemical vapor deposition method. The carbon-based conductive matrix is ​​porous carbon, carbon nanotubes or graphene, the nano-silicon exists in the form of nano-particles or nano-films, the weight percentage in the negative electrode material is 10-90%, and the thickness of the nano-carbon coating layer is 0.1-10nm. However, the volume expansion of nano-silicon is buffered by the carbon-based conductive matrix and the nano-carbon coating, but the effect is limited. As the cycle progresses, the nano-carbon coating is prone to rupture, resulting in repeated regeneration of the SEI film, consumption of reversible lithium, continuous attenuation of the battery capacity, and reduced cycle life. The reversible capacity at 0.1C is 1200mAh / g, and the capacity retention rate after 50 cycles is only 83%.

[0005] Therefore, how to further reduce the volume effect of silicon-based negative electrodes during the charging and discharging process, improve the cycle stability of silicon-based negative electrode batteries, and increase the cycle life is an urgent problem that needs to be solved. Summary of the invention

[0006] The main purpose of the present invention is to provide a silicon-based composite material, a negative electrode, and a battery to solve the problems of poor cycle stability and short cycle life of silicon-based negative electrode batteries in the prior art.

[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a silicon-based composite material is provided, which comprises silicon-carbon composite material particles and a sustained-release substance, wherein the silicon-carbon composite material particles comprise porous carbon and silicon nanomaterials loaded in the pores of the porous carbon, wherein the sustained-release substance is coated on the outer surface of the silicon-carbon composite material particles to form a sustained-release layer; or the sustained-release substance has a three-dimensional network structure at a micron size, and the silicon-carbon composite material particles are dispersed in the three-dimensional network structure of the sustained-release substance.

[0008] Furthermore, in the silicon-based composite material, the content of the sustained-release substance is 0.1-20wt%, more preferably 0.1-10wt%, and further preferably 0.1-5wt%; preferably, in the silicon-based composite material, the content of silicon element is 15-75wt%.

[0009] Furthermore, when the slow-release material is coated on the outer surface of the silicon-carbon composite material particles to form a slow-release layer, the median particle size D of the silicon-carbon composite material particles is V50 The particle size is 6 to 12 μm, and the sustained-release substance is selected from one or more of organic polymers, metal oxygen-containing compounds, and carbon materials.

[0010] Furthermore, when the silicon-carbon composite material particles are dispersed in the three-dimensional network structure of the sustained-release substance, the median particle size D of the silicon-carbon composite material particles is V50 The particle size is 0.1-1 μm, and the sustained-release substance is selected from porous metal oxygen-containing compounds.

[0011] Furthermore, the organic polymer is selected from one or more of starch, oxidized starch, esterified starch, etherified starch, pregelatinized starch, melamine, polyethylene oxide, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile and lithium complexes thereof; and / or the metal oxygen-containing compound is selected from Al2O3, SiO2, Na2O, K2O, MgO, CaO, TiO2, FeO, Fe2O3, ZnO, Ga2O3, Y2O3, ZrO2, AlPO4, Si x One or more of AlPO4, MgSiO3, MgSi2O5, Al(OH)3, AlPO4, Al(PO3)3, Mg(OH)2, Zn(OH)2; and / or, the carbon material is selected from one or more of amorphous carbon, carbon nanoparticles, carbon black, carbon nanotubes, carbon fibers, graphene, pyrolytic carbon, and vapor deposited carbon.

[0012] Furthermore, the porous metal oxygen compound is selected from porous Al2O3, porous SiO2, porous Na2O, porous K2O, porous MgO, porous CaO, porous TiO2, porous FeO, porous Fe2O3, porous ZnO, porous Ga2O3, porous Y2O3, porous ZrO2, porous AlPO4, porous Si xOne or more of AlPO4, porous MgSiO3, porous MgSi2O5, porous Al(OH)3, porous AlPO4, porous Al(PO3)3, porous Mg(OH)2, and porous Zn(OH)2.

[0013] Furthermore, there are lithium-containing compounds on the surface and / or inside the silicon-based composite material, and the lithium-containing compounds are selected from one or more of Li2Si2O5, Li2SiO3, Li4SiO4, LiF, LiOH, Li2CO3, Li3PO4, LiPO3, LiPON, LLTO, LLZO, and LATP; preferably, based on the total mass of the silicon-carbon composite material particles as 100%, the content of the lithium-containing compounds is 3 to 10 wt%.

[0014] Furthermore, the outer surface of the silicon-based composite material is also provided with a coating layer; preferably, the material of the coating layer is selected from one or more of solid electrolytes, conductive polymers, carbonaceous materials, metals, metal oxides, metal hydroxides, metal halides, metal sulfides, metal phosphates, boron-containing compounds, sulfur-containing compounds, nitrogen-containing compounds, halogen-containing compounds, polymetallic oxygenates, etc.; further preferably, the material of the coating layer is selected from carbonaceous materials.

[0015] In order to achieve the above objective, according to one aspect of the present invention, a negative electrode is provided, the negative electrode comprising the aforementioned silicon-based composite material.

[0016] According to another aspect of the present invention, a battery is provided, comprising a positive electrode and the negative electrode described above.

[0017] The sustained-release material can slowly release lithium ions, so that the capacity retention rate is maintained at a high level, which greatly improves the cycle life of the electrode. Such silicon-based composite materials can show excellent cycle performance when applied to lithium-ion batteries. At the same time, the silicon-carbon composite material particles of the present application use porous carbon as a carrier, and load silicon nanomaterials in its pores to obtain a submicron or even nanoscale uniformly mixed silicon-carbon composite material. The pore structure of porous carbon, as a place for the deposition of silicon nanomaterials, can effectively alleviate the volume effect during the insertion and extraction of lithium from silicon nanomaterials in the pores, thereby improving the cycle performance of the composite electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0019] Figure 1 A schematic diagram of the structure of a silicon-based composite material in one embodiment of the present invention is shown;

[0020] Figure 2 A schematic structural diagram of a silicon-based composite material in another embodiment of the present invention is shown. DETAILED DESCRIPTION

[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0022] As described in the background technology section, the existing silicon-based negative electrode battery has the problems of poor cycle stability and short cycle life. In order to solve this problem, the present application provides a silicon-based composite material, the silicon-based composite material comprises silicon-carbon composite material particles and a slow-release substance, the silicon-carbon composite material particles include porous carbon and silicon nanomaterials loaded in the pores of the porous carbon; Figure 1 As shown, the slow-release material is coated on the outer surface of the silicon-carbon composite material particles to form a slow-release layer; or, as Figure 2 As shown, the sustained-release substance has a three-dimensional network structure at the micron size, the silicon-carbon composite material particles are dispersed in the three-dimensional network structure of the sustained-release substance, and the sustained-release substance constitutes a sustained-release matrix in the silicon-based composite material.

[0023] The sustained-release material can slowly release lithium ions, so that the capacity retention rate is maintained at a high level, which greatly improves the cycle life of the electrode. Such silicon-based composite materials can show excellent cycle performance when applied to lithium-ion batteries. At the same time, the silicon-carbon composite material particles of the present application use porous carbon as a carrier, and load silicon nanomaterials in its pores to obtain a submicron or even nanoscale uniformly mixed silicon-carbon composite material. The pore structure of porous carbon, as a place for the deposition of silicon nanomaterials, can effectively alleviate the volume effect during the insertion and extraction of lithium from silicon nanomaterials in the pores, thereby improving the cycle performance of the composite electrode.

[0024] In some embodiments, when the slow-release material is coated on the outer surface of the silicon-carbon composite material particles to form a slow-release layer, the median particle size D of the silicon-carbon composite material particles is V50 The sustained-release material is selected from one or more of organic polymers, metal oxygen compounds, and carbon materials. Preferably, the lithium ion conductivity of the sustained-release layer is 0.01 to 10 mS / cm.

[0025] In other embodiments, when the silicon-carbon composite material particles are dispersed in the three-dimensional network structure of the sustained-release substance, the median particle size D of the silicon-carbon composite material particles is V50 The particle size is 0.1-1 μm, and the sustained-release substance is selected from porous metal oxygen-containing compounds.

[0026] The organic polymer is selected from one or more of starch, oxidized starch, esterified starch, etherified starch, pregelatinized starch, melamine, polyethylene oxide, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile and lithium complexes thereof. The metal oxygen-containing compound is selected from Al2O3, SiO2, Na2O, K2O, MgO, CaO, TiO2, FeO, Fe2O3, ZnO, Ga2O3, Y2O3, ZrO2, AlPO4, Si x One or more of AlPO4 (x is 0.01 to 500), MgSiO3, MgSi2O5, Al(OH)3, AlPO4, Al(PO3)3, Mg(OH)2, and Zn(OH)2. The carbon material is selected from one or more of amorphous carbon, carbon nanoparticles, carbon black, carbon nanotubes, carbon fibers, graphene, pyrolytic carbon, and vapor deposited carbon. The porous metal oxygen-containing compound is selected from porous Al2O3, porous SiO2, porous Na2O, porous K2O, porous MgO, porous CaO, porous TiO2, porous FeO, porous Fe2O3, porous ZnO, porous Ga2O3, porous Y2O3, porous ZrO2, porous AlPO4, porous Si x One or more of AlPO4, porous MgSiO3, porous MgSi2O5, porous Al(OH)3, porous AlPO4, porous Al(PO3)3, porous Mg(OH)2, and porous Zn(OH)2.

[0027] In order to further balance the electrochemical performance and cycle stability of the battery, in some embodiments, the content of silicon in the silicon-based composite material is 15-75 wt %.

[0028] In some embodiments, in the silicon-based composite material, the content of the sustained-release substance is 0.1 to 20 wt %, more preferably 0.1 to 10 wt %, and further preferably 0.1 to 5 wt %.

[0029] In some embodiments, the silicon nanomaterial is silicon nanoparticles and / or silicon nanowires. Preferably, the particle size of the silicon nanoparticles is 0.5-10 nm, and the diameter of the silicon nanowires is 0.5-10 nm.

[0030] In order to further improve the electrochemical performance of the battery, a lithium-containing compound is also present on the surface or inside of the silicon-based composite material (for example, in the porous carbon pores, in the three-dimensional network structure), and the lithium-containing compound is selected from one or more of Li2Si2O5, Li2SiO3, Li4SiO4, LiF, LiOH, Li2CO3, Li3PO4, LiPO3, LiPON (lithium phosphorus oxygen nitrogen), LLTO (lithium lanthanum titanium oxide), LLZO (lithium lanthanum zirconium oxide), and LATP (lithium aluminum titanium phosphate). Preferably, the content of the lithium-containing compound is 3 to 10 wt % based on the total mass of the silicon-based composite material particles as 100%.

[0031] In order to further improve the cycle stability of the battery, in some embodiments, the outer surface of the silicon-based composite material is further provided with a coating layer; preferably, the material of the coating layer is selected from one or more of solid electrolytes, conductive polymers, carbonaceous materials, metals, metal oxides, metal hydroxides, metal halides, metal sulfides, metal phosphates, boron-containing compounds, sulfur-containing compounds, nitrogen-containing compounds, halogen-containing compounds, polymetallic oxygenates, etc.; further preferably, the material of the coating layer is selected from carbonaceous materials.

[0032] For example, the solid electrolyte is selected from one or more of LISICON solid electrolytes, NASICION solid electrolytes, perovskite solid electrolytes, garnet solid electrolytes or sulfide solid electrolytes; the conductive polymer is selected from one or more of polyethylene oxide, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile and lithium complexes thereof; the carbonaceous material is selected from one or more of carbon nanotubes, graphene, carbon black or carbon fiber; the metal is selected from one or more of lithium, magnesium, copper, nickel, aluminum or silver; the metal oxide is selected from one or more of aluminum oxide, zinc oxide, magnesium oxide, zirconium oxide or titanium oxide; the metal hydroxide is selected from one or more of lithium hydroxide, magnesium hydroxide or zinc hydroxide; the metal phosphate is selected from one or more of lithium phosphate, aluminum phosphate or lithium aluminum phosphate.

[0033] The present application also provides a method for preparing the aforementioned silicon-based composite material, comprising the following steps:

[0034] A1: Provide porous carbon;

[0035] A2: Using silicon-containing gas as deposition gas, silicon nanomaterials are deposited in the pores of porous carbon by chemical vapor deposition process to obtain silicon-carbon composite material particles;

[0036] A3: A sustained-release layer is provided on the surface of the silicon-carbon composite material particles to obtain a silicon-based composite material.

[0037] In the above step A1, the porous carbon can be commercially available porous carbon conventionally used in the art, without particular limitation. Alternatively, it can be prepared by pyrolysis and / or activation of a carbon precursor (e.g., a polymer precursor, a biomass precursor, and a fossil carbon source), which are conventionally known to those skilled in the art and will not be described in detail herein.

[0038] In step A2, the silicon-containing gas is in contact with the porous carbon at 200-1000° C. for 0.1-100 hours, and silicon nanoparticles and / or silicon nanowires are loaded in the pores of the porous carbon by chemical vapor deposition. Preferably, the silicon-containing gas is selected from one or more of monosilane, disilane, trisilane, halogenated silane, polysilane, silole and its derivatives, silanol and its derivatives; more preferably, an inert gas is used as a carrier gas for the silicon-containing gas, and the inert gas is selected from one or more of nitrogen, argon or helium, and the volume content of the silicon-containing gas is 1-50%.

[0039] By in-situ forming silicon nanoparticles and / or silicon nanowires in the pores of porous carbon by chemical vapor deposition (CVD), smaller-sized silicon nanomaterials can be obtained, which effectively alleviates the volume expansion of the composite material caused by the lithium-silicon alloying reaction and improves the cycle stability of the composite material electrode.

[0040] In step A3, a sustained-release layer can be formed on the surface of the silicon-carbon composite material particles by spray drying or in-situ growth, and the sustained-release layer includes one or more of an organic polymer, a metal oxygen-containing compound, and a carbon material. In some embodiments, the preparation can be carried out according to the following steps: the silicon-carbon composite material particles obtained by A1 are uniformly dispersed in a solution or dispersion of an organic polymer, spray-dried, and a silicon-based composite material with sustained release of an organic polymer is obtained. In some embodiments, the silicon-based composite material containing an organic polymer sustained-release layer is sintered to obtain a silicon-based composite material with sustained release of a carbon material. In some embodiments, the silicon-carbon composite material particles obtained by A1 are dispersed in a solution containing metal ions, and a silicon-based composite material with sustained release of a metal oxygen-containing compound is obtained by sintering after in-situ precipitation or directly sintering and in-situ decomposition.

[0041] The present application also provides another method for preparing the aforementioned silicon-based composite material, comprising the following steps:

[0042] B1: Providing a sustained-release matrix with a three-dimensional network structure;

[0043] B2: impregnating / filling the carbon precursor into the three-dimensional network structure of the sustained-release matrix and carbonizing it to obtain a composite matrix;

[0044] B3: Using silicon-containing gas as deposition gas, silicon nanomaterials are deposited in the pores of the material obtained in B2 by chemical vapor deposition to obtain a silicon-based composite material.

[0045] In the above step B1, the sustained-release matrix is ​​a metal oxygen-containing compound, and a commercially available porous metal oxygen-containing compound can be used.

[0046] In step B2, a carbon precursor is impregnated / filled in the three-dimensional network structure of the sustained-release matrix, and the carbon precursor is selected from one or more of glucose, sucrose, maltose, lactose, cyclodextrin, starch, glycogen, cellulose, hemicellulose, lignin, epoxy resin, thermoplastic phenolic resin, thermosetting phenolic resin, polyoxymethylene resin, urea-formaldehyde resin, furfural resin, furfural ketone resin, acrylic resin, coconut shell, rice shell or wood. The material is carbonized at a carbonization temperature of 600 to 1800° C. for 0.5 to 10 hours, thereby forming porous carbon attached to the surface of the porous sustained-release matrix to obtain a porous composite matrix.

[0047] In a preferred embodiment, the composite matrix is ​​activated by contacting the composite matrix with one or more of H2O, CO2, O2 or O3 at a temperature of 300 to 1000°C for 0.5 to 20 hours; or, the composite matrix is ​​mixed with one or more of NaOH, KOH, Na2CO3, K2CO3, potassium acetate, Na2O, K2O, Na2O2, K2O2, Na2O, K2O, H3PO4 or ZnCl2 and then incubated at a temperature of 600 to 1500°C in an inert atmosphere. The composite matrix is ​​first contacted with one or more of H2O, CO2, O2 or O3 at a temperature of 300-1000°C for 0.5-20h, and then the composite matrix is ​​mixed with one or more of NaOH, KOH, Na2CO3, K2CO3, potassium acetate, Na2O, K2O, Na2O2, K2O2, Na2O, K2O, H3PO4 or ZnCl2 and treated under an inert atmosphere at a temperature of 600-1500°C for 0.5-30h.

[0048] Step B3 is the same as the chemical vapor deposition step in the aforementioned method, and will not be described again. In the obtained silicon-based composite material, the silicon nanomaterial is dispersed in the pores of the composite matrix, and is combined with the porous carbon loaded on the surface of the sustained-release matrix in the composite matrix to form a silicon-carbon composite material, and the sustained-release matrix forms a three-dimensional network structure surrounding the silicon-carbon composite material.

[0049] In order to further improve the electrochemical performance of the battery, preferably after step A2 or step B3, the preparation method also includes the step of pre-lithiation treatment of the obtained material. The pre-lithiation treatment is carried out by vapor deposition, thermal doping, oxidation-reduction or electrochemical method. These methods are all commonly used pre-lithiation means in the art, and the specific process is not repeated in this application. Preferably, the lithium source for the pre-lithiation treatment is selected from lithium element and / or lithium-containing compounds; further preferably, the lithium-containing compound is selected from one or more of lithium oxide, lithium hydroxide, lithium carbonate, lithium hydride, lithium nitride, lithium fluoride, lithium chloride or lithium bromide.

[0050] In order to further improve the cycle stability of the battery, in some embodiments, preferably after step A2 and / or step A3, the preparation method further includes the step of performing a first coating treatment on the silicon-carbon composite material particles or performing a second coating treatment on the silicon-based composite material. In other embodiments, preferably after step B3, the preparation method further includes the step of performing a first coating treatment and / or a second coating treatment on the silicon-based composite material. Preferably, the first coating treatment and the second coating treatment are performed by chemical vapor deposition coating, atomic layer deposition coating, sol-gel coating, hydrothermal / solvothermal coating.

[0051] The present application also provides a negative electrode, including the aforementioned silicon-based composite material. Based on the above reasons, the silicon-based composite material prepared by the present application effectively alleviates the large volume expansion of silicon in the composite electrode, delays the capacity decay during the cycle process, and solves the technical problem of short cycle life of composite electrode in the prior art.

[0052] The present application also provides a battery, including a positive electrode and the aforementioned negative electrode. Based on the above reasons, the silicon-based composite material prepared by the present application effectively alleviates the large volume expansion of silicon in the composite electrode, delays the capacity decay during the cycle process, and solves the technical problem of short cycle life of composite electrode in the prior art.

[0053] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0054] Example 1

[0055] Step S1: Raise the temperature of sucrose to 800°C at 2°C / min in a N2 atmosphere and maintain it for 2 hours. After crushing and grading, a porous carbon material is obtained.

[0056] Step S2: placing the porous carbon material in a fixed bed, raising the temperature from room temperature to 600°C at 2°C / min in a N2 atmosphere; then changing to a 20% SiH4-N2 mixed gas, and maintaining it at 600°C for 30 hours in a 20% SiH4-N2 mixed atmosphere; changing to a N2 atmosphere, and naturally cooling it under the protection of N2, and after crushing and grading, obtaining silicon-carbon composite material particles.

[0057] Step S3: Disperse silicon-carbon composite material particles, starch and AlPO4 in water, add LiOH aqueous solution, and stir thoroughly to form a slurry; use spray granulation equipment for granulation, with an inlet air temperature of 250°C and an outlet temperature of 90°C. The obtained material is sintered at 500°C to obtain a silicon-based composite material with a silicon content of 52wt%.

[0058] Example 2

[0059] The silicon-based composite material obtained in Example 1 was evenly mixed with Li3N powder, placed in a high-temperature furnace, heated from room temperature to 800°C at 2°C / min in a N2 atmosphere, and maintained at this temperature for 2h. Li3N was pyrolyzed at high temperature, and active lithium was inserted into the interior of the material to complete pre-lithiation, thereby obtaining a silicon-based composite material.

[0060] The silicon content is 50wt% and the lithium silicate content is 5wt%.

[0061] Example 3

[0062] The silicon-carbon composite material particles prepared in Example 1 were loaded into a CVD furnace, and propylene with a flow rate of 9 L / min and argon with a flow rate of 18 L / min were introduced for a deposition time of 1 hour. Propylene was cracked at high temperature, and pyrolytic carbon was coated on the surface of the particles to obtain a carbon-coated silicon-based composite material with a silicon content of 48 wt%.

[0063] Example 4

[0064] The silicon-based composite material obtained in Example 3 was mixed with lithium carbonate, uniformly dispersed in pure water, stirred evenly and then spray-dried to obtain a silicon-based composite material double-layered with cracked carbon and lithium carbonate, with a silicon content of 45 wt%.

[0065] Example 5

[0066] Step S1: Porous Al2O3 (specific surface area of ​​600m 2 / g) and an aqueous solution of sucrose are mixed evenly, stirred until dry, so that the sucrose is filled in the pores of the porous Al2O3, and the temperature is increased to 800°C at 2°C / min in a N2 atmosphere and maintained for 2h; a composite matrix with porous carbon filled in the pores of the porous Al2O3 is obtained.

[0067] Step S2: placing the composite matrix in a fixed bed, heating the matrix from room temperature to 600°C at 2°C / min in a N2 atmosphere; then changing to a 20% SiH4-N2 mixed gas, and maintaining the mixed gas at 600°C for 30 hours in the 20% SiH4-N2 mixed atmosphere; changing to a N2 atmosphere, and cooling the mixed gas naturally under the protection of N2 to obtain a silicon-based composite material with a silicon content of 50%.

[0068] Example 6

[0069] Compared with Example 5, the difference is that step S1 also includes activating the composite matrix, specifically: heating the composite matrix obtained in step S1 to 900° C. in a 20% CO2-N2 mixed gas and maintaining the temperature for 2 hours to obtain a composite matrix.

[0070] Example 7

[0071] The silicon-based composite material obtained in Example 5 was evenly mixed with Li3N powder, placed in a high-temperature furnace, heated from room temperature to 800°C at 2°C / min in a N2 atmosphere, and maintained at this temperature for 2h. Li3N was pyrolyzed at high temperature, and active lithium was inserted into the interior of the material to complete pre-lithiation, thereby obtaining a silicon-based composite material.

[0072] The silicon content is 37wt% and the lithium silicate content is 5wt%.

[0073] Example 8

[0074] The silicon-based composite material prepared in Example 5 was placed in a CVD furnace, and propylene with a flow rate of 9 L / min and argon with a flow rate of 18 L / min were introduced for a deposition time of 1 hour. Propylene was cracked at high temperature, and pyrolytic carbon was coated on the surface of the particles to obtain a carbon-coated silicon-based composite material with a silicon content of 32 wt%.

[0075] Example 9

[0076] The silicon-based composite material obtained in Example 8 and lithium carbonate were mixed, uniformly dispersed in pure water, stirred evenly and then spray-dried to obtain a silicon-based composite material double-layered with cracked carbon and lithium carbonate, with a silicon content of 30 wt%.

[0077] Comparative Example 1

[0078] Sucrose was heated to 800 °C at 2 °C / min in a N2 atmosphere and maintained at this temperature for 2 h to obtain porous carbon.

[0079] The porous carbon is placed in a fixed bed and heated from room temperature to 600°C at 2°C / min in a N2 atmosphere; then the atmosphere is changed to a 20% SiH4-N2 mixed gas and maintained at 600°C for 30 hours in the 20% SiH4-N2 mixed atmosphere; the atmosphere is changed to a N2 atmosphere and the temperature is naturally lowered under the protection of N2, and after crushing and grading, a silicon-carbon-silicon-based composite material is obtained.

[0080] Among them, the silicon content is 52wt%.

[0081] Performance characterization:

[0082] Electrode, half-cell preparation and electrochemical performance testing:

[0083] The silicon-based composite materials prepared in the examples and comparative examples were used as negative electrode active materials to prepare negative electrode sheets, and the negative electrode sheets were used to prepare CR2032 button batteries using conventional methods, and the batteries were tested for electrical properties. The specific test methods are:

[0084] (1) Half-cell assembly: CR2032 button cells were assembled in a glove box, with lithium metal sheets as counter electrodes, polypropylene microporous membranes as separators, and the electrolyte being LiPF6 dissolved in a mixture of ethyl carbonate (EC) and diethyl carbonate (DEC) (volume ratio EC:DEC = 1:1), where the LiPF6 concentration was 1 mol / L.

[0085] The battery is charged and discharged using the LAND battery testing system.

[0086] (2) Cyclic gram capacity and first efficiency test: After the CR2032 battery is left uncharged for 6 hours, it is discharged at 0.1C to 0.005V, and the capacity is recorded as Q1; it is then discharged at a constant voltage of 0.005V until the current is cut off at 0.01C, and the total capacity is recorded as Q2; after standing for 5 minutes, it is charged at a constant current of 0.1C to 1.5V; the first lithium removal gram capacity is the gram capacity (or mass specific capacity) of the electrode material, and the ratio of the first lithium removal capacity to the first lithium insertion capacity is the first coulombic efficiency of the battery.

[0087] (3) Capacity retention rate test: After standing for 5 minutes, repeat the above charge and discharge steps twice; then discharge to 0.005V at 0.25C; after standing for 5 minutes, charge to 1.5V at 0.25C constant current, and cycle 50 times. The capacity retention rate is calculated as the charge capacity of the 50th cycle / the charge capacity of the 1st cycle × 100%.

[0088] (4) The constant current charging ratio is Q1 / Q2.

[0089] Table 1

[0090]

[0091]

[0092] As shown in Table 1, compared with Comparative Example 1, when the silicon-based composite material has a slow-release layer or a slow-release matrix, the slow-release material can slowly release lithium ions, so that the capacity retention rate is maintained at a high level, and the resulting composite electrode exhibits excellent cycle performance, with a gram capacity retention rate greater than 85% and an electrode expansion rate less than 110%. In Example 2 and Example 7, lithium salts are doped into the silicon-based composite material to supplement the irreversible lithium loss and improve the first effect; from Examples 3 to 4 and Examples 8 to 9, it can be seen that the carbon coating layer can further improve the cycle performance of the silicon-based composite material, and the double-layer coated silicon-based composite material has better electrochemical properties; Compared with Example 5, Example 6 adds a step of activating the composite matrix, so the silicon-based composite material contains ultra-micro pores, which can improve the cycle stability of the silicon-based composite material.

[0093] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A silicon-based composite material, characterized in that: The silicon-based composite material comprises silicon-carbon composite material particles and a slow-release substance. The silicon-carbon composite material particles include porous carbon and silicon nanomaterials loaded in the pores of the porous carbon, wherein: The slow-release substance is coated on the outer surface of the silicon-carbon composite material particles to form a slow-release layer; or The sustained-release substance has a three-dimensional network structure at a micron size, and the silicon-carbon composite material particles are dispersed in the three-dimensional network structure of the sustained-release substance.

2. The silicon-based composite material according to claim 1, characterized in that: In the silicon-based composite material, the content of the sustained-release substance is 0.1 to 20 wt %, more preferably 0.1 to 10 wt %, and further preferably 0.1 to 5 wt %; Preferably, in the silicon-based composite material, the content of silicon element is 15-75wt%.

3. The silicon-based composite material according to claim 1 or 2, characterized in that: When the slow-release material is coated on the outer surface of the silicon-carbon composite material particles to form the slow-release layer, the median particle size D of the silicon-carbon composite material particles is V50 The particle size is 6 to 12 μm, and the sustained-release substance is selected from one or more of organic polymers, metal oxygen-containing compounds, and carbon materials.

4. The silicon-based composite material according to claim 1 or 2, characterized in that: When the silicon-carbon composite material particles are dispersed in the three-dimensional network structure of the sustained-release substance, the median particle size D of the silicon-carbon composite material particles is V50 The particle size is 0.1-1 μm, and the sustained-release substance is selected from porous metal oxygen-containing compounds.

5. The silicon-based composite material according to claim 3, characterized in that: The organic polymer is selected from one or more of starch, oxidized starch, esterified starch, etherified starch, pregelatinized starch, melamine, polyethylene oxide, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile and lithium complexes thereof; And / or, the metal oxygen compound is selected from Al2O3, SiO2, Na2O, K2O, MgO, CaO, TiO2, FeO, Fe2O3, ZnO, Ga2O3, Y2O3, ZrO2, AlPO4, Si x One or more of AlPO4, MgSiO3, MgSi2O5, Al(OH)3, AlPO4, Al(PO3)3, Mg(OH)2, Zn(OH)2; And / or, the carbon material is selected from one or more of amorphous carbon, carbon nanoparticles, carbon black, carbon nanotubes, carbon fibers, graphene, pyrolytic carbon, and vapor deposited carbon.

6. The silicon-based composite material according to claim 4, characterized in that: The porous metal oxygen-containing compound is selected from porous Al2O3, porous SiO2, porous Na2O, porous K2O, porous MgO, porous CaO, porous TiO2, porous FeO, porous Fe2O3, porous ZnO, porous Ga2O3, porous Y2O3, porous ZrO2, porous AlPO4, porous Si x One or more of AlPO4, porous MgSiO3, porous MgSi2O5, porous Al(OH)3, porous AlPO4, porous Al(PO3)3, porous Mg(OH)2, and porous Zn(OH)2.

7. The silicon-based composite material according to claim 1, characterized in that: A lithium-containing compound also exists on the surface and / or inside of the silicon-based composite material, and the lithium-containing compound is selected from one or more of Li2Si2O5, Li2SiO3, Li4SiO4, LiF, LiOH, Li2CO3, Li3PO4, LiPO3, LiPON, LLTO, LLZO, and LATP; Preferably, based on 100% of the total mass of the silicon-carbon composite material particles, the content of the lithium-containing compound is 3-10 wt%.

8. The silicon-based composite material according to claim 1, characterized in that: The outer surface of the silicon-based composite material is also provided with a coating layer; preferably, the material of the coating layer is selected from one or more of solid electrolytes, conductive polymers, carbonaceous materials, metals, metal oxides, metal hydroxides, metal halides, metal sulfides, metal phosphates, boron-containing compounds, sulfur-containing compounds, nitrogen-containing compounds, halogen-containing compounds, polymetallic oxygenates, etc.; further preferably, the material of the coating layer is selected from the carbonaceous material.

9. A negative electrode, characterized in that The negative electrode comprises the silicon-based composite material according to any one of claims 1 to 8.

10. A battery, characterized in that: It comprises a positive electrode and the negative electrode according to claim 9.

Citation Information

Patent Citations

  • Carbon / silicon / carbon nano composite structure cathode material and preparation method thereof

    CN102214817A

Cited By

  • Modified silicon-carbon composite material as well as preparation method and application thereof

    CN120784351A

  • A modified silicon-carbon composite material, a preparation method and application thereof

    CN120784351B

  • Porous carbon material, preparation method thereof and silicon-carbon composite material

    CN121536929A